(untitled) (Law, State and Telecommunications Review, 2021)
[Purpose] This article is devoted to the study of the problem of authorization of the removal of electronic media according to Russian Criminal Procedure Code. [Methodology] The methodological basis of this study is a set of methods of scientific knowledge, among which the main place is taken by the methods of historicism, consistency, analysis and comparative law. The authors’ position is based on the legislation and opinions of the competent scientific environment on the need to use special knowledge in the investigation and seizure (copying) of electronic information relevant to the criminal case. [Findings] Based on a legal analysis of the rules of criminal procedure authors argue the necessity to use specialists in the field of information and communication technologies in inspections, searches, and seizures. The systematization of rules-exceptions that must be observed by investigators during inspections, searches, and seizures is carried out. The questions of the evidentiary value of the results of electronic withdrawal are raised.